They stole our hearts - Kraus, Daniel, 1975- (Kraus, Daniel, 1975- Teddies saga, 2022)
The clever, brave, and sweet teddy bears Buddy, Sunny, and Sugar, together with Reginald the wise, thought they had found a forever home with the child called Darling--but then Darling's mother found where they were hiding, and, like all adults who find them, she reacted with fear and anger, ripping apart one of them before their eyes. The remaining three escape the house and seemingly miraculously find a civilization of similarly discarded teddy bears. However, there is something just "off" about these new bears the three discover.